Cosmopolitan and Ethnic-specific Replication of Genetic Risk Factors for Asthma in Two Latino Populations - Galanter, Joshua M (2011)
BACKGROUND: Although Mexicans and Puerto Ricans are jointly classified as “Hispanic/Latino”, there are significant differences in asthma prevalence, severity, and mortality between the two groups. We sought to examine the possibility that population-specific genetic risks contribute to this disparity. OBJECTIVES: Over 100 candidate genes have been associated with asthma and replicated in an independent population, and seven genomewide association studies in asthma have been performed. We compared the pattern of replication of these associations in Puerto Ricans and Mexicans. METHODS: We genotyped Mexican and Puerto Rican trios using an Affymetrix 6.0 Genechip, and used a family based analysis to test for genetic associations in 124 genes previously associated with asthma. RESULTS: We identified 32 SNPs in 17 genes associated with asthma in at least one of the two populations. Twenty-two of these SNPs in eleven genes were significantly associated with asthma in the combined population and showed no significant heterogeneity of association, while five SNPs were associated in only one population and showed statistically significant effect heterogeneity. In a gene-based approach, two additional genes were associated with asthma in the combined population and three additional genes displayed ethnic-specific associations with heterogeneity. CONCLUSIONS: Our results show that only a minority of genetic association studies replicate in our population of Mexican and Puerto Rican asthmatics. Among SNPs that were successfully replicated, most showed no significant heterogeneity across populations. However, we identified several population-specific genetic associations.